Analisis Pemangku Kepentingan Pada Pengelolaan Ekowisata di Siberut Selatan Kepulauan Mentawai, Indonesia - Rahmanita, Myrza; Asmaniati, Fetty; Agung, Anak Agung Gde; Muhardiansyah, Doni; Mariati, Sri (Jurnal Ilmiah Pariwisata, 2022)
South Siberut District on Mentawai Island has great ecotourism potential however its management is not yet optimal, including synergy and connectivity between stakeholders. This research was conducted using stakeholder analysis method and snowball sampling technique with expert judgment. The informants involved were twelve institutions representing four types of stakeholders, namely the Government, Community, Business, and Academics. The objective of this study is to identify stakeholders involved in ecotourism management; to classify and matrix their level of influence and interest. The significance of this research is to increase cooperation between stakeholders through optimizing their respective roles in South Mentawai. This study finds that, Firstly, the importance of government authority in ecotourism management; Secondly, half of all stakeholders have high interest, while the other half show low and very low interest in supporting ecotourism management; Third, half of all stakeholders are Crowd Stakeholders who have the potential to influence the overall management of ecotourism in the future. It is recommended that efforts should be made to inspire as many parties as possible to be involved as stakeholders. Secondly, increasing the competency capacity of human resources through education. Thirdly, synergizing cooperation and collaboration. Keywords: Stakeholder Analysis, Ecotourism Management, Interest and Influence, Siberut Mentawai